2017
DOI: 10.1007/s12029-017-9930-0
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Combination Chemotherapy in Elderly Pancreatic Cancer: a Review

Abstract: Identifying elderly patients who will benefit from combination chemotherapy for pancreatic cancer remains a significant clinical challenge. An assessment of medical comorbidities and functional status plays a key role in determining fitness for intensive chemotherapeutic regimens in this important subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Some studies, including meta-analyses, have been conducted on chemotherapy for patients aged 65 years and older[ 8 , 11 ]. These studies showed that combination chemotherapy was more effective than G mono.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, including meta-analyses, have been conducted on chemotherapy for patients aged 65 years and older[ 8 , 11 ]. These studies showed that combination chemotherapy was more effective than G mono.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that pancreatic cancer is mainly a disease of the elderly, current clinical trials have underrepresented this important demographic. Their comorbidities and performance status would render the toxicity profile of FOLIRINOX more potent (66) and therefore unacceptable hence these studies may not be applicable to the majority of patients (67). Thus, selection bias means that cohorts of patients undergoing NAT tend to be younger and fitter than an unselected cohort of patients with BRPC.…”
Section: Survival Treatment and Selection Biasmentioning
confidence: 99%
“…PC affects older patients, and the median age at diagnosis is 70 years (Howlader et al, ). Fit older patients with PC have the same benefits from curative surgery and combination chemotherapy regimens as younger patients (Garcia & Odaimi, ; King et al, ).…”
Section: Introductionmentioning
confidence: 99%